Kidnapped But Not Kids: A Case Series of Three Octogenarian Hostages - A. Mark Clarfield; Hagai Levine (Rambam Maimonides Medical Journal, 2024)
On 7 October, 2023 Israel was attacked over the Gaza border by Hamas terrorists. Mostly civilians, approximately 1,200 people were killed, with an additional 251 taken hostage (in addition to 4 abducted before October 7 for a total of 255 hostages), many of whom have since died. Of the total abducted, 13% were older than 65, a third of whom were octogenarians. Brief case histories of three abductees over 80 years of age are presented: two released and one still in captivity. The extreme “pre-morbid” vulnerability of these older hostages is described along with the additional data on their clinical situation and the extreme stresses to which they are being subjected. The situation described constitutes one of the most severe examples of elder abuse documented in the modern era.